2020
DOI: 10.9734/ijtdh/2020/v41i1430348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Disorder Symptoms and Relationship with Work Posture among Staff of a Nigerian University

Abstract: Background: Improper work postures have been associated with many detrimental health outcomes including musculoskeletal disorders. Emerging evidence however suggests that some of these health concerns may be lessened by reducing sedentary behaviour at work. Musculoskeletal disorders have been ranked top among the most prevalent health problems relating directly to working conditions. Aim: This study was thus aimed at determining the prevalence of musculoskeletal disorder symptoms and their relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A Nigerian study showed that, there is higher incidence of WMSDs with effect on their total work efficiency among university staffs (Oluka, et al, 2020). Also, a statistically significant association was found to exist between work posture and quality of work output (Ojule et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A Nigerian study showed that, there is higher incidence of WMSDs with effect on their total work efficiency among university staffs (Oluka, et al, 2020). Also, a statistically significant association was found to exist between work posture and quality of work output (Ojule et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…Work-related musculoskeletal disorders have been identified with a wide range of inflammatory and degenerative conditions affecting the muscles, ligaments, tendon, nerves, bones, and joints which can occur from a single or cumulative trauma (Allsop et al, 2010). Common symptoms of WMSDs are pain, aching, stiffness, fatigue, discomfort, tingling sensations and any of these could appear in the shoulder, upper back, chest, elbow, neck, wrist, lower abdomen, hip, knee or ankle (Ojule et al, 2020). Risk factors for WMSDS are enumerated involving work ergonomics, such as awkward position in sitting and standing while using instrument of workplace.…”
Section: Introductionmentioning
confidence: 99%